Asnaf satisfaction with zakat distribution in Pahang: An analysis of key issues and recommendations - Roslan, Mohammad Nasrul Hakim; Mustapha, Ramlan; Ayub , Mohd Nasir; Ibrahim, Nurshahira; Ibrahim, Rasyad Afif (Journal of Islamic, Social, Economics and Development, 2025)
Zakat, one of the five pillars of Islam, is a compulsory act of giving a portion of one’s wealth to eligible recipients. It functions as a tool for wealth redistribution and social equity. The beneficiaries of zakat, known as asnaf, are divided into eight categories as mentioned in the Qur’an including the poor (fuqara’), the needy (masakin), zakat administrators, those whose hearts are to be reconciled, those in bondage, individuals in debt, those striving in the path of Allah, and stranded travelers. Zakat plays a critical role in reducing poverty and promoting social welfare in Muslim communities. This study explores the distribution of zakat by the Majlis Ugama Islam dan Adat Resam Melayu Pahang (MUIP) in Pahang, Malaysia. It focuses on the adequacy of the aid provided, recipients’ satisfaction, and the challenges faced by asnaf. Using a qualitative method, interviews were conducted with 30 zakat recipients across four regions in Pahang. The results indicate that while zakat aid offers crucial support, it often does not fully meet recipients’ basic needs. Although beneficiaries appreciate the assistance, they expressed concerns over rising living expenses, limited usage flexibility, and challenges in accessing aid. The study also identifies systemic issues, such as the need for improved monitoring, more adaptable distribution mechanisms, and enhanced support in areas like education and healthcare. Recommendations are proposed to strengthen zakat management and enhance its effectiveness in addressing poverty.